An on-chip polarization splitter based on the radiation loss in the bending hybrid plasmonic waveguide structure - Sun, Chengwei; Rong, Kexiu; Gan, Fengyuan; Chu, Saisai; Qihuang Gong; Jianjun Chen* (Applied Physics Letters, 2017)
Polarization beam splitters (PBSs) are one of the key components in the integrated photonic circuits. To increase the integration density, various complex hybrid plasmonic structures have been numerically designed to shrink the footprints of the PBSs. Here, to decrease the complexity of the small hybrid structures and the difficulty of the hybrid micro-nano fabrications, the radiation losses are utilized to experimentally demonstrate an ultra-small, broadband, and efficient PBS in a simple bending hybrid plasmonic waveguide structure. The hybrid plasmonic waveguide comprising a dielectric strip on the metal surface supports both the transverse-magnetic (TM) and transverse-electric (TE) waveguide modes. Because of the different field confinements, the TE waveguide mode has larger radiation loss than the TM waveguide mode in the bending hybrid strip waveguide. Based on the different radiation losses, the two incident waveguide modes of orthogonal polarization states are efficiently split in the proposed structure with a footprint of only about 2.2 × 2.2 μm2 on chips. Since there is no resonance or interference in the splitting process, the operation bandwidth is as broad as Δλ = 70 nm. Moreover, the utilization of the strongly confined waveguide modes instead of the bulk free-space light (with the spot size of at least a few wavelengths) as the incident source considerably increases the coupling efficiency, resulting in a low insertion loss of <3 dB.